COVID-19 and myotonic dystrophy: Case reports and systematic review - Maria Mazzitelli; Marco Trevenzoli; Monica Brundu; Giulia Squarzoni; Anna Maria Cattelan (Journal of Infection in Developing Countries)
Introduction: Steinert's disease is a rare genetic disorder characterized by progressive myotonia and multi-organ damage. It is associated with respiratory and cardiological complications often leading patients to exitus. These conditions are also traditional risk factors for severe COVID-19. SARS-CoV-2 has affected people with chronic diseases, but the impact on people with Steinert's disease is poorly defined, with only a few reported and described. More data are needed to understand whether this genetic disease is a risk factor for more serious evolution or death in patients with COVID-19.